Identification of some biochemical indicators to indicate the contamination of some fish farms in Hilla city/ Iraq (Baghdad Science Journal, 2024)
In order to establish the possibility of determined biochemical indicators of possible pollution in Al-Forat fish farm (A) and Hussein Ajimi fish farm (B) as well as wild fish samples as a control from Shatt Al-Hilla River (C). Oxidative stress factors and antioxidant enzyme activity were determined in common carp Cyprinus carpio blood serum from two fish farms. Reactive Oxygen Species (ROS), Superoxide Dismutase (SOD), Catalase (CAT), Glutathione peroxidase (GPx) and Hydrogen peroxide (H2O2) performance were chosen as pollution bioindicators, as well as Total Protein (TP) as a general bio indicator for fish health. Results showed an increase in all antioxidant enzymes activities and oxidative stress factors in fishes from station B which recorded 34.52 μg/ml, 81.46 U/ml, 75.55 KU/L, 4.36 ± 0.4 U/l, 11.82 nmol and 41.13 mg/l for ROS, SOD, CAT, GPx, H2O2 and TP respectively in a significant difference (P < 0.05) from stations A and C, which indicate the heighten of pollution in the Hussein Ajimi fish farm B than from Al-Forat fish farm A and the control fish from Shatt Al-Hilla River C. The study confirms the possibility of using oxidative stress factors and antioxidant enzymes as biochemical indicators of fish farms pollution.